Pengaruh Kepemimpinan Situasional, Kinerja Kerja Guru Terhadap Disiplin Peserta Didik Di SMP Negeri 1 Taopa Kabupaten Parigi Moutong - Muslim Muslim; Syafruddin Syafruddin; Sunarto Amus (ITB AAS Indonesia Surakarta, 2024)
This study aims to evaluate the influence of principals' situational leadership and teachers' performance on students' discipline at SMP Negeri 1 Taopa, Parigi Moutong. The research method used is descriptive quantitative, with data collection through questionnaires, interviews, and documentation. The results of data analysis using multiple linear regression with SPSS version 16 show that there is no significant effect of situational leadership of the principal (X1) or teacher performance (X2) on student discipline (Y). Likewise, there is no joint influence between principals' situational leadership and teachers' performance on students' discipline. This conclusion is based on the significance value (sig) which is greater than the significance level set (0.05). These findings provide insights for schools to improve leadership strategies and teacher performance to improve learner discipline. Keywords: situational leadership, teacher performance, student discipline